Antimicrobial activity of various extracts of whole plant of Anisomeles malabarica (Linn.) R. Br. - R. Ranganathan*, R. Vijayalakshmi and (International Multidisciplinary Research Journal, 2011)
<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;">Anisomeles malabarica <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;">(Linn.) R.Br. is a traditional medicinal plant of Lamiaceae family, distributed throughout India. All the three extracts petroleum ether, Ethyl Acetate, methanol of Anisomeles malabarica (Linn.) R.Br. were tested for Antimicrobial efficacy against gram positive and gram negative bacterial and then fungal organisms. The methanolic extract of Anisomeles malabarica (Linn.) R.Br. were exhibited maximum antibacterial and anti fungal activity when compared with other two extracts. Hence it can be concluded that the methanolic extract of Anisomeles malabarica (Linn.) R.Br. possess a significant Antimicrobial activity. This also stands as a scientific support for the usage of this plant for wound healing.